Dioscin from smilax china rhizomes inhibits platelet activation and thrombus formation via up-regulating cyclic nucleotides - Ga Hee Lee; Jin Pyo Lee; Na Yoon Heo; Chang-Dae Lee; Gyeongchan Kim; Akram Abdul Wahab; Man Hee Rhee; Sanghyun Lee; Dong-Ha Lee (Scientific Reports)
Abstract Cardiovascular disease, the leading cause of mortality in the United States, is caused by abnormal platelet accumulation and coagulation. Dioscin has been reported to suppress the growth of tumor-associated cells and trigger apoptosis. However, its mechanism in inhibiting platelet activation has not been confirmed. This study investigates whether dioscin from Smilax china rhizomes exerts antithrombotic effects by regulating the activation of human platelets and explains its mechanism of action. Dioscin increased the production of cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP). This increase induced the phosphorylation of inositol 1,4,5-triphosphate receptor (IP3R), which inhibited the dense Ca2+ release channels, thereby reducing Ca2+ mobilization. Furthermore, it promoted the phosphorylation of vasodilator-stimulated phosphoprotein (VASP), which suppressed integrin αIIbβ3 and fibrinogen binding, thus inhibiting platelet activation. Dioscin regulated phosphorylation of phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt), mitogen-activated protein kinase (MAPK) and cytosolic phospholipase A2 (cPLA2), which are proteins associated with platelet granule release. Finally, ingestion of S. china rhizomes containing dioscin significantly inhibited thrombus formation in the FeCl3-induced thrombosis model. Therefore, dioscin from S. china rhizomes exhibited antiplatelet effects that could delay or halt thrombus formation by regulating the phosphorylation of various signaling molecules and related proteins, thus suggesting dioscin’s potential value for development as an antithrombotic agent.